2022
DOI: 10.3389/fphar.2022.885259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implementation of DPYD Pharmacogenetic Testing to Prevent Early-Onset Fluoropyrimidine-Related Toxicity in Cancer Patients in Switzerland

Abstract: The implementation of pharmacogenetic testing into clinical practice has been a slow process so far. Here, we review the implementation of pre-treatment testing of dihydropyrimidine dehydrogenase gene (DPYD) risk variants to prevent early-onset fluoropyrimidine (FP)-related toxicity in cancer patients in Switzerland based on data of a large Swiss diagnostic center. In January 2017, the Swiss Federal Office of Public Health introduced the reimbursement of DPYD testing by the compulsory health insurance in Switz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“… 35 A study by Begré et al. 36 noticed that oncologists who were part of research collaborations related to DPD deficiency testing were ‘early adopters’ of DPD deficiency testing in clinical practice. This highlights how knowledge about clinical relevance impacts implementation of the test.…”
Section: Discussionmentioning
confidence: 99%
“… 35 A study by Begré et al. 36 noticed that oncologists who were part of research collaborations related to DPD deficiency testing were ‘early adopters’ of DPD deficiency testing in clinical practice. This highlights how knowledge about clinical relevance impacts implementation of the test.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment DPYD variant screening can present a significant impact on the number of genotyping tests, constituting a challenge in terms of health care resources. Nonetheless, several studies have demonstrated that upfront genotyping of DPYD variants is feasible and cost-saving while preventing severe toxicity [20,26,28,29,38,43,44]. In this work, we describe a genotyping assay using KASP methodology for the four DPYD variants associated with fluoropyrimidine toxicity that current guidelines recommend testing for.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggested that upfront genotyping of DPYD variants followed by individualized dose adjustment would improve the safety of fluoropyrimidine therapy for patients and reduce overall treatment costs [17,20,[24][25][26][27][28][29]. On 13 March 2020, the European Medicines Agency's (EMA's) Pharmacovigilance Risk Assessment Committee has recommended that patients receiving fluorouracil given by injection or infusion and the related medicines capecitabine and tegafur should be tested for the lack of DPD enzyme, either by measuring the level of uracil in the blood or DPYD gene variant analysis, before starting treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Early prospective data and health economic modelling illustrate the cost‐effectiveness of upfront DPYD genotyping across various health systems internationally, and upfront DPYD genotyping has become part of the standard of care in the Netherlands, France, Switzerland, Germany, and the United Kingdom. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Although there is limited information on the international uptake of testing, for pharmacogenomics generally and DPYD specifically, increases in uptake of DPYD genotyping rose by 14% following endorsement of pre‐emptive screening by the European Medicines Agency in 2020, showing the impact of both clinical champions and early adopters on the implementation of health practices. 26 , 27 To date, pre‐emptive DPYD screening has not been adopted systematically in Australia.…”
mentioning
confidence: 99%
“… 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Although there is limited information on the international uptake of testing, for pharmacogenomics generally and DPYD specifically, increases in uptake of DPYD genotyping rose by 14% following endorsement of pre‐emptive screening by the European Medicines Agency in 2020, showing the impact of both clinical champions and early adopters on the implementation of health practices. 26 , 27 To date, pre‐emptive DPYD screening has not been adopted systematically in Australia.…”
mentioning
confidence: 99%